Evaluation of Outdoor Physical Maintenance in the Rectorate Area of the University of Indonesia - Rizal Maulana Ardani Satrio Anggoro; Qurrotu ‘Aini Besila; Rini Fitri; Eko Adhy Setiawan (Universitas Trisakti, 2023)
The University of Indonesia boasts numerous green open spaces, including the Rector's Area. However, both the softscape and hardscape elements of the University of Indonesia Rectorate Area need to be well-maintained. The outdoor space's physical maintenance needs to meet standard requirements. This study aims to describe the softscape and hardscape conditions in the rectorate area of the University of Indonesia. Qualitative methods were employed for this investigation. Data was gathered via direct observations and interviews concerning the maintenance conditions at the University of Indonesia campus. A descriptive data analysis was conducted to discuss the identified problems. The findings indicate that the Rectorate Area of the University of Indonesia covers both softscape and hardscape maintenance activities. The maintenance of trees, shrubs, and plants aligns with the existing standards, while hardscape maintenance fails to meet these requirements due to several substandard elements. These maintenance issues encompass bus stops, bicycle stands, pedestrian pavements, and seating areas. Attention must be paid to various aspects, including rust, as this indicates the need for repainting.